2022
DOI: 10.12998/wjcc.v10.i3.830
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic approach for managing intussusception in children: Analysis of 65 cases

Abstract: BACKGROUND Intussusception can be managed by pneumatic reduction, ultrasound-guided hydrostatic reduction, open or laparoscopic surgery, but laparoscopy in such cases remains controversial. AIM To explore the clinical characteristics, effectiveness, and complications of surgical reduction for intussusception using laparoscopy in children. METHODS This study was a retrospective case series of pediatric patients with intussusception who underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Wang (2010) [10] reported a similar case in a 10-year-old male who presented with intussusception and acute appendicitis secondary to ileocecal Burkitt lymphoma. This finding correlates with that reported by Sheng-Miao (2022) [9], Tomography allows thorough characterization of the lesion, vascular compromise, and related complications, as well as the cause of intussusception (anatomic abnormalities or tumor processes) [12].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Wang (2010) [10] reported a similar case in a 10-year-old male who presented with intussusception and acute appendicitis secondary to ileocecal Burkitt lymphoma. This finding correlates with that reported by Sheng-Miao (2022) [9], Tomography allows thorough characterization of the lesion, vascular compromise, and related complications, as well as the cause of intussusception (anatomic abnormalities or tumor processes) [12].…”
Section: Discussionsupporting
confidence: 89%
“…followed by ileoileocolic, colocolic, ileocolocolic, ileoileal, and jejunojejunal [5][6][7][8][9]. In the present case, the ileocolic location associated with appendiceal invagination is described, leading to acute appendicitis that required surgical resolution.…”
Section: Discussionmentioning
confidence: 65%
“…A recent study revealed a case of small bowel obstruction in a total of 100 children who had laparotomy without ileopexy [ 18 ]. In contrast, in another recently published study, it was shown that no small intestine adhesion or obstruction occurred in a total of 61 children who had ileopexy [ 19 ].…”
Section: Discussionmentioning
confidence: 95%
“…It is speculated that bowel resection removes the segment responsible for intussusception, thereby preventing recurrence [ 16 ]. Although at a very low rate, intestine adhesion and obstruction can occur after either laparoscopic or open surgical reduction of intussusception [ 17 19 ]. However, direct comparison of this complication in children with simple surgical induction and those with surgical induction plus ileopexy has not been described.…”
Section: Discussionmentioning
confidence: 99%
“…Intussusception is a form of intestinal obstruction in which a segment of the bowel prolapses into a more distal segment. Li CL et al [ 5 ]. reported that the proportion of intussusception secondary to intestinal polyps in children was 12.96%.…”
Section: Discussionmentioning
confidence: 99%